In Situ Nucleic Acid Amplification and Ultrasensitive Colorimetric Readout in a Paper‐Based Analytical Device Using Silver Nanoplates. Issue 7 (30th November 2020) - Suea‐Ngam, Akkapol; Choopara, Ilada; Li, Shangkun; Schmelcher, Mathias; Somboonna, Naraporn; Howes, Philip D.; deMello, Andrew J.
Abstract: A rapid, highly sensitive, and quantitative colorimetric paper‐based analytical device (PAD) based on silver nanoplates (AgNPls) and loop‐mediated isothermal amplification (LAMP) is presented. It is shown that cauliflower‐like concatemer LAMP products can mediate crystal etching of AgNPls, with a threefold signal enhancement versus linear dsDNA. Methicillin‐resistant Staphylococcus aureus (MRSA), an antimicrobial resistant bacterium that poses a formidable risk with persistently high mortality, is used as a model pathogen. Due to the excellent color contrast provided by AgNPls, the PAD allows qualitative analysis by the naked eye and quantitative analysis using a smartphone camera, with detection limits down to a single copy in just 30 min, and a linear response from 1 to 10 4 copies ( R 2 = 0.994). The entire assay runs in situ on the paper surface, which drastically simplifies operation of the device. This is the first demonstration of single copy detection using a colorimetric readout, and the developed PAD shows great promise for translation into an ultrasensitive gene‐based point‐of‐care test for any infectious disease target, via modification of the LAMP primer set. Abstract : The combination of loop‐mediated isothermal amplification (LAMP) and silver nanoplates allows ultrasensitive colorimetric detection of methicillin‐resistant Staphylococcus aureus (MRSA), down to a single target copy, with easy qualitative readout by the naked eye and quantitative readout with a smartphone camera.